Algebra


  1. If x +
    1
    = 2 ,find the value of 8x3 +
    1
    .
    2xx3









  1. View Hint View Answer Discuss in Forum

    Using Rule 8,

    x +
    1
    = 2
    2x

    ⇒ 2x +
    2
    = 2 × 2 = 4
    2x

    ⇒ 2x +
    1
    = 4
    x

    On cubing both sides,
    ∴ 8x3 +
    1
    + 3 × 2x ×
    1
    2x +
    1
    = 64
    x3xx

    ⇒ 8x3 +
    1
    + 6 × 4 = 64
    x3

    ⇒ 8x3 +
    1
    = 64 – 24 = 40
    x3

    Correct Option: C

    Using Rule 8,

    x +
    1
    = 2
    2x

    ⇒ 2x +
    2
    = 2 × 2 = 4
    2x

    ⇒ 2x +
    1
    = 4
    x

    On cubing both sides,
    ∴ 8x3 +
    1
    + 3 × 2x ×
    1
    2x +
    1
    = 64
    x3xx

    ⇒ 8x3 +
    1
    + 6 × 4 = 64
    x3

    ⇒ 8x3 +
    1
    = 64 – 24 = 40
    x3


  1. If x = a +
    1
      and y = a -
    1
      then the value of x4 + y4 - 2x2y2 is
    aa









  1. View Hint View Answer Discuss in Forum

    Given , a +
    1
    + 1 = 0
    a

    x4 + y4 - 2x2y2 = ( x2 - y2 )2
    = [ ( x + y )( x - y ) ]2
    = a +
    1
    + a -
    1
    a +
    1
    - a +
    1
    2
    aaaa

    = 2a ×
    2
    2 = 16
    a

    Correct Option: C

    Given , a +
    1
    + 1 = 0
    a

    x4 + y4 - 2x2y2 = ( x2 - y2 )2
    = [ ( x + y )( x - y ) ]2
    = a +
    1
    + a -
    1
    a +
    1
    - a +
    1
    2
    aaaa

    = 2a ×
    2
    2 = 16
    a



  1. If x1 / 3 + y1 / 3 = z1 / 3 , then {(x + y – z)3 + 27xyz} equals :









  1. View Hint View Answer Discuss in Forum

    Using Rule 8,
    x1 / 3 + y1 / 3 = z1 / 3 ......(i)
    Cubing both sides,
    ( x1 / 3 + y1 / 3 = z1 / 3 )3 = z
    ⇒ x + y + 3 x1 / 3 . y1 / 3 ( 1 / 3 + y1 / 3 ) = z
    [∴ (a + b)3 = a3 + b3 + 3ab (a + b)]
    ⇒ x + y – z = - 3 x1 / 3 . y1 / 3 .z1 / 3 ......(ii) [From equation (i)]
    ∴ (x + y – z)3 + 27xyz = [ - 3x1 / 3 . y1 / 3 . z1 / 3 ]3 + 27xyz [From equation (ii)]
    = – 27xyz + 27xyz = 0

    Correct Option: C

    Using Rule 8,
    x1 / 3 + y1 / 3 = z1 / 3 ......(i)
    Cubing both sides,
    ( x1 / 3 + y1 / 3 = z1 / 3 )3 = z
    ⇒ x + y + 3 x1 / 3 . y1 / 3 ( 1 / 3 + y1 / 3 ) = z
    [∴ (a + b)3 = a3 + b3 + 3ab (a + b)]
    ⇒ x + y – z = - 3 x1 / 3 . y1 / 3 .z1 / 3 ......(ii) [From equation (i)]
    ∴ (x + y – z)3 + 27xyz = [ - 3x1 / 3 . y1 / 3 . z1 / 3 ]3 + 27xyz [From equation (ii)]
    = – 27xyz + 27xyz = 0


  1. If 2p +
    1
    = 4 , then the value of p3 +
    1
    is
    p8p3









  1. View Hint View Answer Discuss in Forum

    Using Rule 8,

    2p +
    1
    = 4
    p

    ⇒ p +
    1
    = 2
    2p

    p +
    1
    3 = p3 +
    1
    + 3 × p ×
    1
    p +
    1
    2p8p32p2p

    ⇒ 8 = p3 +
    1
    +
    3
    × 2
    8p32

    ⇒ p3 +
    1
    = 8 - 3 = 5
    8p3

    Correct Option: B

    Using Rule 8,

    2p +
    1
    = 4
    p

    ⇒ p +
    1
    = 2
    2p

    p +
    1
    3 = p3 +
    1
    + 3 × p ×
    1
    p +
    1
    2p8p32p2p

    ⇒ 8 = p3 +
    1
    +
    3
    × 2
    8p32

    ⇒ p3 +
    1
    = 8 - 3 = 5
    8p3



  1. If 4b2 +
    1
    = 2 , then the value of8b3 +
    1
    is
    b2b3









  1. View Hint View Answer Discuss in Forum

    Using Rule 1,

    2b +
    1
    2 = 4b2 +
    1
    + 2 × 2b ×
    1
    = 2 + 4 = 6
    bb 2b

    ⇒ 2b +
    1
    = √6
    b

    ∴ 8b3 +
    1
    = 2b +
    1
    3 - 3 × 2b ×
    1
    2b +
    1
    b3bbb

    = ( √6 )3 - 6( √6 ) = 6 √6 - 6 √6 = 0

    Correct Option: A

    Using Rule 1,

    2b +
    1
    2 = 4b2 +
    1
    + 2 × 2b ×
    1
    = 2 + 4 = 6
    bb 2b

    ⇒ 2b +
    1
    = √6
    b

    ∴ 8b3 +
    1
    = 2b +
    1
    3 - 3 × 2b ×
    1
    2b +
    1
    b3bbb

    = ( √6 )3 - 6( √6 ) = 6 √6 - 6 √6 = 0